DETEKSI FRAUDULENT FINANCIAL REPORTING: GABUNGAN MODEL BENEISH M-SCORE DAN ALTMAN Z-SCORE - Gusnan Mulyadi; Eddy Suranta; Pratana Puspa Midiastuty; Anton Robiansyah (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to provide empirical evidence of the influence of financial leverage ratios, profitability, asset composition, and liquidity on fraudulent financial reporting). This study uses agency theory and GONE theory. The population used is manufacturing companies listed on the Indonesia Stock Exchange with an observation period of 2010-2021. The sample used was 75 companies with a total of 207 observations. The dependent variable in this study is fraudulent financial reporting which is a categorical variable that is a combination of the Beneish M-Score and Altman Z-Score models and the independent variables used are the ratio of financial leverage, profitability, asset composition, and liquidity. Testing the hypothesis using logistic regression and the results of the study prove that profitability, asset composition, and liquidity affect the probability of fraudulent financial reporting